THE ROLE OF SOFT SKILLS IN ENSURING THE SUSTAINABLE DEVELOPMENT OF ORGANIZATIONS IN THE CONTEXT OF GLOBAL CHALLENGES - Buchynska, Tetiana (МІЖНАРОДНА ЕКОНОМІКА В УМОВАХ КЛІМАТИЧНИХ ЗМІН: ГЛОБАЛЬНІ ВИКЛИКИ, 2026)
.